2013
DOI: 10.12659/msm.884024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methoxy polyethylene glycol-epoetin beta on oxidative stress in predialysis patients with chronic kidney disease

Abstract: BackgroundThere is data in the literature indicating increased oxidative stress in chronic kidney disease (CKD). Erythropoiesis-stimulating agents (ESAs), which are commonly used to treat anemia in patients with CKD, seem to have an antioxidant action, which could be a part of nephroprotection. The aim of the current study was to investigate the effect of a long half-life ESA, methoxy polyethylene glycol-epoetin beta (Mircera), on some markers of oxidative stress in predialysis patients with CKD.Material/Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…These data are extremely important to avoid misinterpretations, as it was previously shown that any imbalance between α and β chains of hemoglobin (α or β-thalassemia, respectively) plays a crucial role in OS [27] . Besides, there are data linking the observed levels of the various biomarkers evaluated in this study to health outcomes, such as in renal failure [28] and breast cancer [29] . Taking into account our results and those previously found, it is plausible to assume that under blood transfusion therapy, the excess of labile (catalytically active) iron must generate free radicals via Fenton chemistry, resulting in oxidative damage to biomolecules in vivo [30] .…”
Section: Discussionmentioning
confidence: 97%
“…These data are extremely important to avoid misinterpretations, as it was previously shown that any imbalance between α and β chains of hemoglobin (α or β-thalassemia, respectively) plays a crucial role in OS [27] . Besides, there are data linking the observed levels of the various biomarkers evaluated in this study to health outcomes, such as in renal failure [28] and breast cancer [29] . Taking into account our results and those previously found, it is plausible to assume that under blood transfusion therapy, the excess of labile (catalytically active) iron must generate free radicals via Fenton chemistry, resulting in oxidative damage to biomolecules in vivo [30] .…”
Section: Discussionmentioning
confidence: 97%
“…Oxidative stress can result in mitochondrial injury, nutritional impairment, and DNA damage in diabetic patients [15,16]. Bartnicki et al [17 ]showed that methoxy polyethylene glycol-epoetin beta improves systemic oxidative stress in predialysis chronic kidney disease patients. Dang et al [18] demonstrated that epoetin beta prevents reactive oxygen species generation and prevent high glucose-induced renal cell apoptosis in diabetic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…A search of the literature shows that recombinant human erythropoietin and its synthetic derivatives (at least epoetin beta and methoxy polyethylene glycol-epoetin beta) have anti-oxidant, anti-inflammatory and cytoprotective properties [17,18,19,22,23,24,25]. But it cannot be concluded that different synthetic derivatives of epoetin may offer the same effects on cytoprotection, possibly a result that may reflect different affinities binding to the EPOR.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigations clearly showed that oxidative stress and inflammatory factors were links between CKD and cardiovascular complications [ 13 , 14 ]. Very recently, some studies found that methoxy polyethylene glycol-epoetin beta may inhibit oxidative stress through enhancing the antioxidant defense system and reducing reactive oxygen species (ROS) in predialysis patients with CKD [ 15 ], Yimaz MI and Xu G et al [ 16 , 17 ] reported that estimated GFR was negatively associated with malondialdehyde concentration and positively correlated with ROC activity, and that oxidative stress and inflammation alter GFR when CKD develops, which could indicate that oxidative stress and inflammation in the body cause decreased GFR.…”
Section: Discussionmentioning
confidence: 99%